Achieving Latina students: Aspirational counterstories and critical reflections on parental community cultural wealth. Issue 4 (2nd October 2018) - Aragon, Antonette
ABSTRACT: In this study, six Latina students shared perceptions of their parental influence on their educational aspirations. CRT, LatCrit, and community cultural wealth provide the tripartite framework for analyzing issues of race, class, gender, language, culture, and immigration by examining their roles in society through counterstories. Learning in an after-school program about educational advancement, these participants navigated against deficit ideology. Messages of aspirational hope, navigational inspiration, Spanish language guidance, familial kinship, social networking, and resistant intelligence enabled these students to build a foundation of personal emancipation to disrupt the systemic sociopolitical and sociocultural nature of oppression.